Assessment of Treg-related lncRNAs in epilepsy - Sharifi, Guive; Eghtedarian, Reyhane; Taheri, Mohammad; Hussen, Bashdar Mahmud; Eslami, Solat; Ghafouri-Fard, Soudeh; Sayad, Arezou (Frontiers in Molecular Neuroscience, 2023)
Recent studies have shown dysregulation of several groups of long non-coding RNAs in the context of epilepsy. According to evidence regarding the role of regulatory T cells in this disorder, we examined expression levels of regulatory T cell-related lncRNAs, namely TH2-LCR, RMRP, IFNG-AS1 (NEST), MAFTRR and FLICR in the blood of epileptic cases compared with controls. Expression of RMRP was lower in patients with refractory epilepsy compared with controls (expression ratio (95% CI)= 0.32 (0.13-0.8), adjusted P value=0.0008). Besides, its expression was lower in refractory patients versus non-refractory patients (expression ratio (95% CI)= 0.2 (0.1-0.41), adjusted P value<0.0001). Expression of TH2-LCR was lower in refractory patients versus controls (expression ratio (95% CI)= 0.4 (0.17-0.93), adjusted P value=0.0044) and in refractory patients versus non-refractory ones (Expression ratio=0.28 (0.19-0.58), P value<0.0001). Expression of NEST was higher in total patients (expression ratio (95% CI)= 2.48 (1.15-5.27), adjusted P value=0.0012) and in both groups of patients compared with controls. However, its expression was not different between refractory and non-refractory cases. Similarly, FLICR and MAFTRR were over-expressed in total cases and both groups of patients compared with controls, but their expressions were similar between refractory and non-refractory cases. MAFTRR could differentiate between total epileptic cases and controls with AUC value of 0.8. This lncRNA could separate refractory and non-refractory cases from healthy controls with AUC values of 0.73 and 0.88, respectively. This study provides evidence for deregulation of regulatory T cell-related lncRNAs in epilepsy and their potential role as diagnostic markers in this condition.